Mockingjay - Collins, Suzanne (2010)
Katniss Everdeen's having survived the Hunger games twice makes her a target of the Capitol and President Snow, as well as a hero to the rebels who will succeed only if Katniss is willing to put aside her personal feelings of anger and distrust and serve as their pawn. She must accept responsibility for countless lives in order to change the course of the future of Panem. District 13 really does exist. There are rebels. There are new leaders. A revolution is unfolding.
Ashes -- Assault -- Assassin.
Young Adult.
Interest age level : Ages 13-17.
Lexile: 800L.
Keywords: Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Science fiction; Dystopian fiction; Novels; Young adult fiction